Understanding State Democracy Issues Based on Global Literature - Adil Hassan Ibrahim; Akhmad Zaim Hasan; Salahudin (Konsultan Surya Buanan, 2024)
This research aims to find out the progress of the state democracy study. The research method applied to this research is systematic literature review using 60 scientific articles sourced from databse scopus. The results reveal the relationship between state and democracy. We explore the concept of state democracy studies, focusing on the role of civil society and deliberative democracies in shaping state-to-community relations. In this Systematic Literature Review (SLR), we present a comprehensive synthesis of the latest literature that focuses on the role of states in facilitating and strengthening democracy. In addition, in the Systematic Literatur Review, we examine the various forms of deliberative processes and their implications for relations between states and societies. These findings suggest that deliberative democracy can promote a more inclusive and participatory political system, in which civil society plays an important role in shaping public policies and making states accountable. We identify trends, key concepts, and challenges faced in understanding the dynamics of democracy in various country contexts. Our findings highlight the importance of accountability, citizen participation, and the role of institutions in achieving sustainable democracy. This research provides an in-depth insight for academics, practitioners, and policymakers to understand the complexity of the relationship between state and democracy. The results of this research have contributed to the development of studies on the subject of state democracy. The limitation of this research is that articles are used only from scopus databases so the research findings cannot comprehensively describe the issues of state democracy. Further research needs to use scientific articles that come from other reputable international database sources, such as the Web of Science and Dimensionds Scholars.